2020
DOI: 10.1519/jsc.0000000000003555
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng Supplementation Increases Muscle Recruitment, Attenuates Perceived Effort, and Accelerates Muscle Force Recovery After an Eccentric-Based Exercise in Athletes

Abstract: Cristina-Souza, G, Santos-Mariano, AC, Lima-Silva, AE, Costa, PL, Domingos, PR, Silva, SF, Abreu, WC, De-Oliveira, FR, and Osiecki, R. Panax Ginseng supplementation increases muscle recruitment, attenuates perceived effort, and accelerates muscle force recovery after an eccentric-based exercise in athletes. J Strength Cond Res 36(4): 991–997, 2022—The effect of Panax ginseng during and after an eccentric-based exercise is underexplored. In this study, we investigated the effect of Panax ginseng on muscle force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Gislaine Cristina-Souza et al [ 28 ] reported a better response in muscle excitation and subjective perception of effort due to the consumption of 100 mg/kg/day of PG in 10 athletic subjects after eccentric strength work. This is the only randomised intervention study with crossover groups in which the subjects analyzed are athletes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gislaine Cristina-Souza et al [ 28 ] reported a better response in muscle excitation and subjective perception of effort due to the consumption of 100 mg/kg/day of PG in 10 athletic subjects after eccentric strength work. This is the only randomised intervention study with crossover groups in which the subjects analyzed are athletes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we obtain objective evidence on the direct relationship between ginseng consumption and muscle regeneration. On the other hand, Cristina-Souza [ 28 ] and her collaborators studied muscle regeneration of subjects through voluntary muscle excitation. In this article, it was found that those who used the PG supplement recovered muscle arousal levels after exercise more quickly than those who did not ingest it.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT hyperactivity in the CNS is the most well-known alteration in neurotransmitters that inhibits proprioceptive sensory and muscular contractions [ 28 ]. Ginseng improves physical function in both healthy individuals and subjects complaining of fatigue [ 14 , 29 ]. Likewise, in the present study, KRG improved exercise performance in the rotarod test under both normal conditions and after SD ( Figure 2 B,C).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of ginseng has been associated with improved muscle force recovery following muscle-damaging exercise when taken acutely, in two doses (4000 mg pre- and post-exercise) [ 241 ] or for 8 days (100 mg/day) spanning the pre- and post-exercise periods [ 242 ], despite no concurrent change in blood markers of muscle damage [ 241 , 242 ]. There is also some evidence that acute (5000 mg) [ 243 ] or longer-term (1200 mg/day for 4 weeks) [ 244 ] supplementation with ginseng may reduce blood markers of muscular fatigue (lactate) following exercise.…”
Section: Herbal Supplementsmentioning
confidence: 99%